A higher-education teaching module for integrating industry content and language through online recruitment advertisements - Tatzl, Dietmar (Studies in Second Language Learning and Teaching, 2018)
Empirical evaluations of practical teaching units integrating content and language in higher education are rare and deserve more attention. The current article aims to narrow this gap by providing an empirical study of an integrating content and language in higher education (ICLHE, Smit & Dafouz, 2012) teaching module. It investigates the effectiveness of a content-based English for specific purposes module in tertiary aeronautical engineering education, which incorporates recruitment advertisements as online resources. The study adopted a mixed-methods approach and surveyed three aeronautical engineering student groups (N = 141) over three consecutive years on their perceptions of the module’s learning outcomes. This longitudinal survey was complemented by a teacher-assessed writing task and a qualitative content analysis of online recruitment advertisements (N = 80) in a self-built corpus. All three year groups rated the 10 questionnaire statements on a 5-point Likert scale rather equally, thus suggesting a similar perception of academic achievement stemming from the module’s completion. This student view was supported by the results of the writing assignment. In short, the module’s effectiveness was corroborated both quantitatively and qualitatively, which identifies this teaching concept as a feasible way forward.